AN EXPERIMENTAL STUDY OF THE CONVECTIVE HEAT TRANSFER ENHANCEMENT: APPLICATION OF TURBULENCE PROMOTERS - Zdanski, P. S. B.; Bublitz, A. E.; Correa, C. N. (Revista de Engenharia Térmica, 2013)
This work presents an experimental study addressing the effects of turbulence promoters on heat transfer rate at circular cylinder in external cross flow. Within this framework, the work focuses on assessing the effects of three kind of turbulence promoters (with circular, square and hexagonal cross sections) on convective heat transfer enhancement. The distance from turbulence promoters to the circular cylinder (50, 100 and 150mm upstream), as well as the free stream velocity inside the wind tunnel (Reynolds number) were the parameters investigated. The validation of the experimental methodology was performed by comparing the present results with empiric correlations available in the literature. The main results indicate that the convective heat transfer coefficient was enhanced when using turbulence promoters. The highest heat transfer enhancement obtained was around 25% correponding to the case of square turbulence promoter placed closely (50mm) to the circular cylinder. Finally, it is worth mentioning that all the experimental results for the convective coefficient were condensed in a new empirical correlation with good accuracy.